2010
DOI: 10.1007/s11274-010-0331-9
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of benzene by pure and mixed cultures of Bacillus spp.

Abstract: Benzene has a wide range of industrial applications, but it is also a major source of environmental pollution. The most eco-friendly/cost-effective method of remediation is biodegradation. In the present study, we used a variety of microbial strains in different combinations on a selection of substrate concentrations to determine the most effective degradation processes. Bacterial strains of pure culture (L 4 , N 3 , and N 6 ) were isolated from oil sludge in both Luria-Bertani buffer (LB) and nutrient broth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…This indicated removal of gasoline by biological activity. Our results were similar to a study conducted by Liu et al [27]. They observed that Bacillus isolates: Bacillus sp.…”
Section: Growth and Biodegradation Potential Towards Gasoline Of B Subtilis Se1supporting
confidence: 93%
“…This indicated removal of gasoline by biological activity. Our results were similar to a study conducted by Liu et al [27]. They observed that Bacillus isolates: Bacillus sp.…”
Section: Growth and Biodegradation Potential Towards Gasoline Of B Subtilis Se1supporting
confidence: 93%
“…The results suggested that the genera of Bacillus were found to be predominant and involved in benzene biodegradation. This finding is supported by Liu et al [43].…”
Section: Molecular Characterization (16s Rrna) Of Bacterial Isolatesupporting
confidence: 78%
“…Beyond 40 mL•h −1 , the decrease in RE was more sharp which indicates the possibility of change in controlling mechanism in the bioreactor [20][21][22]. Hassan et al [47] reported the benzene loading up to 34.1 g m −3 h −1 and removal efficiency consistently over 98% was achieved while at loading of 76.8 g m −3 h −1 removal efficiency was observed above 80% and 6.9 g m −3 h −1 EC [10,29,31,[42][43][44][45][46][47]. Fig.…”
Section: Biodegradation Of Benzene In Pbbr and Cpbbrmentioning
confidence: 95%
“…Also, the use of bioremediation strategies, being cost effective, entails higher time treatment. Thus, Singh and Fulekar and Liu et al (38,39) concluded remediation levels about 100% for benzene and toluene after a one-week degradation process.…”
Section: Aromatics Extractionmentioning
confidence: 99%